Synthesis and optical properties of lanthanides doped ultrasmall NaYF₄ markers for bio-medical applications - Podhorodecki, A.; Banski, M.; Misiewicz, J. (Вiopolymers and Cell, 2011)
Aim. To synthesise NaYF₄ nanocrytstals doped or co-doped with different lanthanide ions (Eu, Tb, Gd) and to investigate them optically to achieve efficient optical markers. Methods. Samples have been synthesized by using co-thermolizys method and optical properties have been investigated by using photoluminescence (PL), PL excitation and PL decay spectroscopies. Results. Efficient emission in visible spectra range has been observed for all investigated samples. The excitation mechanism of the main emission centre has been explained. Conclusions. It has been shown that the main excitation mechanism of Eu ions is through energy transfer from Tb or Gd ions. Moreover, it has been shown that obtained by us nanocrystals characterize by strong emission which make them potential as efficient optical markers in biology or medicine. Keywords: optical markers, nanocrystals, lanthanides, NaYF₄.